Pengabdian Berbasis Pemberdayaan Masyarakat Pemanfaatan Digitalisasi di Dusun Menggoran II - Jamiludin, Muhammad; Hadziqoh, Zakiyyah; Sukhfi, Muhammad Adnan; Itobi, Mochammad Faza Rusyda; Kurniawan, Rangga Yudha Saputra; Nada, Elsa Julya; Aulia, Azzahra Rizki; Syahrani, Nabila; Arza, Naufal Ahnafi; Afifah, Fa’izah Noor; Darumurti, Awang (Universitas Muhammadiyah Yogyakarta, 2025)
The development of digital literacy in the tourism sector is a strategic step to enhance the community’s ability to manage village potential sustainably. The community empowerment program carried out by the Universitas Muhammadiyah Yogyakarta (UMY) service team in Menggoran 2 Hamlet, Bleberan Village, Playen District, Gunungkidul Regency, aims to improve the community's skills in marketing local tourism potential through digital platforms. The main focus of this program is training in graphic design, videography, and administration so that the community can more effectively promote their tourist attractions. The method used is a participatory approach, where the service team acts as facilitators in the empowerment process. This approach actively involves the community in every stage of the activity, from planning to evaluation. The results of this program show positive impacts, such as an increased understanding of digital marketing and the community’s enthusiasm in utilizing social media for tourism promotion. The community also began to create promotional designs and simple videos to attract tourists. This success demonstrates that digital literacy plays a crucial role in enhancing the competitiveness of local tourism and empowering the community towards a more independent and innovative tourist village